Three new species of Eleutherodactylus (Amphibia: Leptodactylidae) from high elevations of the cordillera Central of Colombia - Lynch John D.; Ruiz Carranza Pedro M.; Ardila Robayo María Cristina (Caldasia, 1996)
A new species of the Eleutherodactylus orcesi group, the smallest member of the group, is described from the Páramo de los Valles (Tolima). It is very similar to E. slmoterus. From the same locality, a new species of dwarf Eleutherodactylus, lacking a tympanum, is described. It appears to be a member of the E. myersi group. Lastly, a new large black Eleutherodactylusis described from páramo and subpáramo habitats of the Cordillera Central. This species is distributed from Antioquia to Cauca. With these three species, fifteen species of Eleutherodactylus are known for páramo and subpáramo habitats of the Cordillera Central north of the Macizo de Pasto. These 15 species be long to tour species groups. Se describe una especie nueva del grupo de Eleutherodactylus orcesi del Páramo de los Valles (Tolima). Esta especie es muy parecida a E. simoterus pero se distingue por su tamaño (la especie nueva es la más pequeña del grupo). Se describe también una especie enanita del Páramo de los Valles que posiblemente es una especie del grupo de Eleutherodactylus myersl. La especie es muy distinta porque carece de tímpano. Finalmente, se describe una especie grande y negra que se encuentra desde Antioquia hacia Cauca en la Cordillera Central. Con estas especies, tenemos 15 especies de Eleutherodactylus conocidas de los páramos y subpáramos de la Cordillera Central al norte del Macizo de Pasto, que pertenecen a cuatro grupos de especies.